Development and use of three-dimensional image analysis algorithms to evaluate puffing of banana slices undergone combined hot air and microwave drying - Maturada Jinorose; A. Satienkijumpai; Sakamon Devahastin (My University, 2018)
Puffing is an attractive alternative for the production of healthy crisp snacks without frying. Although image analysis has been used in some prior studies to evaluate puffing, such an evaluation was made only in one or two dimensions, which is inadequate when a sample deforms in three dimensions. In this study, use of combined hot-air and microwave drying to dry and puff banana slices was first evaluated. Algorithms were then developed to characterize the changes in the appearance of puffed banana slices. Various image-based parameters, both in two and three dimensions were assessed and used to monitor the puffing. Keywords: Deformation; Puffing; Imge analysis; Physical properties; Surface texture
Keywords: Texture (cosmology); Sample (material); Spectroscopy and Chemometric Analyses